Genetic diversity of eggplant germplasm based on agro-morphological traits under open field and glasshouse conditions - Mat Sulaiman, Nur Nadzirah (2020)
Eggplant or brinjal (Solanum melongena L.) is an economically important vegetable crop worldwide. However, cultivation of eggplant in Malaysia is hindered by narrow genetic-based of commercially cultivated varieties. There is a limitation in its genetic diversity study and improvement of local variety that caused the country to depend on importation of eggplant and its seed from neighbouring countries. The main objective of this study was to evaluate the genetic diversity among 29 eggplant accessions from Malaysia, Thailand and China based on agro-morphological traits under two cropping conditions (open field and glasshouse). The specific objectives were to estimate genetic variance and heritability values of the eggplant germplasm and to select the superior accessions for further breeding programmes. The experiments were laid out in a Randomized Complete Block Design (RCBD) with three replications in; open field and glasshouse conditions. Data were collected on vegetative, yield, and yield components, and were subjected to analysis of variance (ANOVA) using SAS version 9.4. The analysis of variance showed highly significant difference (P≤0.01) among accessions for number of primary branches (NPB), plant height (PHE), stem diameter (SDM), days to first flowering (DFF), fruit girth (FGI), diameter of fruit (DFR), fruit length (FLE), fruit length to width ratio (FLW), total number of fruits (TNF), number of fruits per bunch (NFB), average fruit weight (AFW) and fruit yield per plant (FYP). Estimated heritability values ranged from 41.56% (FYP) to 93.08% (TNF) and 26.82% (AFW) to 92.55% (TNF) under open field and glasshouse conditions, respectively. Higher vegetative traits were observed for glasshouse condition while higher mean values for yield and yield components were observed in open field cultivation. These results revealed that open field condition is more suitable for higher yield as compared to glasshouse condition. Additionally, highly significant correlations (P≤0.01) were observed for all traits with the fruit yield per plant except for stem diameter (SDM), days to first flowering (DFF) and number of fruits per bunch (NFB). The evaluated accessions were grouped into six primary clusters based on the assessed traits using multivariate analysis viz. clustering analysis. However, some accessions from different sources were clustered together which implied that there were genetic similarities between Malaysia, Thailand and China accessions. Hence, for high vigour or heterosis, hybridisation could be made between group I with groups IV or V. Out of 29 evaluated accessions, 13MR, 10ML, 3TR, 23ML and 16ML were identified as the best five accessions for yield performance. These accessions are recommended for commercial cultivation under open field condition and have the potential to be utilized in future breeding programmes for new varietal development.